Gestational Diabetes Mellitus and Postpartum Care Practices of Nurse‐Midwives. (14th January 2013) - Ko, Jean Y.; Dietz, Patricia M.; Conrey, Elizabeth J.; Rodgers, Loren; Shellhaas, Cynthia; Farr, Sherry L.; Robbins, Cheryl L.
<x xml:space="preserve">Abstract</x> Introduction: Postpartum screening for glucose intolerance among women with recent histories of gestational diabetes mellitus (GDM) is important for identifying women with continued glucose intolerance after birth, yet screening rates are suboptimal. In a thorough review of the literature, we found no studies of screening practices among certified nurse‐midwives (CNMs). The objectives of our study were to estimate the prevalence of postpartum screening for abnormal glucose tolerance and related care by CNMs for women with recent histories of GDM and to identify strategies for improvement. Methods: From October through December 2010, the Ohio Department of Health sent a survey by mail and Internet to all licensed CNMs practicing in Ohio. We calculated prevalence estimates for knowledge, attitudes, clinical practices, and behaviors related to postpartum diabetes screening. Chi‐square statistics were used to assess differences in self‐reported clinical behaviors by frequency of postpartum screening. Results: Of the 146 CNMs who provided postpartum care and responded to the survey (62.2% response rate), 50.4% reported screening women with GDM‐affected pregnancies for abnormal glucose tolerance at the postpartum visit. Of CNMs who screened postpartum, only 48.4% used fasting blood sugar or the 2‐hour oral glucose tolerance test. Although 86.2% of all responding CNMs reported that they inform women with recent histories of GDM of their increased risk for type 2 diabetes mellitus, only 63.1% counseled these women to exercise regularly and 23.3% reported referring overweight/obese women to a diet support group or other nutrition counseling. CNMs reported that identification of community resources for lifestyle interventions and additional training in postpartum screening guidelines may help to improve postpartum care. Discussion: CNMs in Ohio reported suboptimal levels of postpartum diabetes testing and use of a recommended postpartum test. Providing CNMs with additional training and identifying community resources to support needed lifestyle behavior change may improve care for women with recent GDM‐affected pregnancies.